Evaluating the traditional day and night shift in an acute care surgery fellowship: Is the swing shift a better choice?. Issue 1 (January 2018) - Chestovich, Paul J.; McNicoll, Christopher F.; Ingalls, Nichole K.; Kuhls, Deborah A.; Fraser, Douglas R.; Morrissey, Shawna L.; Fildes, John J.
Abstract : BACKGROUND: Fellowship trainees in acute care surgery require experience in the management of complex and operative trauma cases. Trauma center staffing usually follows standard 12-hour or 24-hour shifts, with resident and fellow trainees following a similar schedule. Although trauma admissions can be generally unpredictable, we analyzed temporal trends of trauma patient arrival times to determine the best time frame to maximize trainee experience during each day. METHODS: We reviewed 10 years (2007–2016) of trauma registry data for blunt and penetrating trauma activations. Hourly volumetric trends were observed, and three specific events were chosen for detailed analysis: (1) trauma activation with Injury Severity Score (ISS) greater than 15, (2) laparotomy for trauma, and (3) thoracotomy for trauma. A retrospective shift log was created, which included day (7:00 AM to 7:00 PM), night (7:00 PM to 7:00 AM), and swing (noon to midnight) shifts. A swing shift was chosen because it captures the peak volume for all three events. Means and 95% confidence intervals were calculated, and comparisons were made between shifts using the Wilcoxon matched-pairs signed rank test with Bonferroni correction, and p less than 0.05 considered significant. RESULTS: During the 10-year study period, 28, 287 patients were treated at our trauma center. This included the evaluation and management of 7, 874 patients with ISS greater than 15, performance of 1, 766 laparotomies, and 392 thoracotomies for trauma. Swing shift was superior to both day and night shifts for ISS greater than 15 ( p < 0.001). Both swing and night shifts were superior to day shift for laparotomies ( p < 0.001). Swing shift was superior to both day shift ( p < 0.001) and night shift ( p = 0.031). Shifts with the highest yield of ISS greater than 15, laparotomies, and thoracotomies include night and swing shifts on Fridays and Saturdays. CONCLUSION: Projected experience of acute care surgery fellows in managing complex trauma patients increases with the integration of swing shifts into the schedule. Daily trauma volume follows a temporal pattern which, when used correctly, can increase trainee exposure to complex and operative trauma cases. We encourage other centers to analyze their volume and adjust trainee schedules accordingly to maximize their educational experience. Level of Evidence: Therapeutic study, level IV.